2016
DOI: 10.1021/acs.molpharmaceut.6b00818
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Transendothelial Electrical Resistance Thresholds for the Study of Small and Large Molecule Drug Transport in a Human in Vitro Blood–Brain Barrier Model

Abstract: A human cell-based in vitro model that can accurately predict drug penetration into the brain as well as metrics to assess these in vitro models are valuable for the development of new therapeutics. Here, human induced pluripotent stem cells (hPSCs) are differentiated into a polarized monolayer that express blood-brain barrier (BBB)-specific proteins and have transendothelial electrical resistance (TEER) values greater than 2500 Ω·cm. By assessing the permeabilities of several known drugs, a benchmarking syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 35 publications
18
65
1
Order By: Relevance
“…Previous work in our lab has shown that with a starting concentration of 10 mg/ml in the luminal compartment, 0.034% crosses into the abluminal compartment after 6 hr (Mantle et al, 2016). This figure falls between the widely accepted statistic of 0.1% of peripheral IgGs able to penetrate the brain (Banks et al, 2002) and 0.009% of peripherally administered IVIG measured in the murine brain (St-Amour et al, 2013).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Previous work in our lab has shown that with a starting concentration of 10 mg/ml in the luminal compartment, 0.034% crosses into the abluminal compartment after 6 hr (Mantle et al, 2016). This figure falls between the widely accepted statistic of 0.1% of peripheral IgGs able to penetrate the brain (Banks et al, 2002) and 0.009% of peripherally administered IVIG measured in the murine brain (St-Amour et al, 2013).…”
Section: Discussionsupporting
confidence: 59%
“…Our previous work has shown that this iPSC-BBB model can be used to study small molecule therapeutics (Mantle et al, 2016), and here we demonstrate its utility in studying the transport of biologics, understanding transport events at the cellular level, and understanding changes to the BBB in disease. IgG transport in the model is saturable, consistent with in vivo IgG transport behavior.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations